Mamíferos em agroecossistemas: abordagens para avaliação da diversidade e exposição a contaminantes - Gomes de Sá, Érica Fernanda Gonçalves (2024)
Agricultural expansion and intensification result in reduced biodiversity due to habitat fragmentation, habitat loss, and exposure to contaminants. These impacts are observed across all levels of biological diversity, including community, population, and individual levels. Our aim was to investigate these impacts using mammals as biomonitors. In Chapter I, the objective was to evaluate mammal exposure in the Brazilian agricultural scenario. We conducted a systematic review on the occurrence of mammals in agroecosystems and based on the environmental risk assessment of pesticides for nontarget organisms (ERA), we evaluated the functional traits of mammals in the main crops. We reviewed 200 studies reporting the occurrence of 319 species, 205 of which were found in crops. Thirty-five endangered species occur in crop, suggesting potential exposure to contaminants. The functional space of mammals indicates that two or three generic model species are required to accurately assess exposure. Based on the probability of occurrence of functional groups across different agroecosystem types, generic model species can be used for pasture systems, tree plantations, and annual crops, mammals with terrestrial, crepuscular traits, medium to large size, and vertebrate diets. In agroforestry and perennial crops, generic model species with arboreal characteristics and frugivorous or nectarivorous diets are recommended. In Chapters II and III, we evaluate a ricePantanal system using small mammals as a case study. In Chapter II, we sampled the small mammal community in the rice paddy and legal reserve until reaching saturation on the species accumulation curve over 12,774 trap nights. We found a high level of differentiation (beta=0.95) when abundance was estimated. The reserve exhibited greater taxonomic diversity. Functional and phylogenetic diversity metrics were higher in the rice paddy than in the reserve when based on incidence, whereas the opposite was observed when based on abundance. Abundance-based metrics are essential for accurately assessing the impact of agroecosystems at the community level. In Chapter III, we assessed the small mammals exposure by quantifying metals in critical tissues and in the soil in rice paddy and reserve. We found high concentrations of cadmium in the liver and kidney of animals from both habitats. Overall, the highest concentrations of non-essential metals, aluminum (605.86 ± 298.10 mg/kg) and lead (74.09 ± 57.71 mg/kg), were observed in the kidneys of rodents from the legal reserve. For the soil, we also observed higher concentrations of the non-essential metals aluminum (4,881.48 ± 1,034.69) and cadmium (0.33 ± 0.20) in the legal reserve. The results of this thesis guide the public regulatory sector and academia in assessing the environmental risk of contaminants to non-target organisms. Through the evaluation of the rice-Pantanal model system, we provide an unprecedented protocol to assess the impacts of agroecosystems on the small mammal community, using multiple diversity metrics and contaminant quantification. This protocol can be replicated in other agricultural systems to expand knowledge about the occurrence and health of mammals in agroecosystems, direct future conservation research, and assist in creating legislation for monitoring contaminants in the environment.